Cryptosporidium sp. skunk genotype in wild raccoons (Procyon lotor) naturally infected with Baylisascaris procyonis from Central Germany. (December 2020) - Rentería-Solís, Zaida; Meyer-Kayser, Elisabeth; Obiegala, Anna; Ackermann, Franziska; Król, Nina; Birka, Stefan
Abstract: Cryptosporidium spp. are apicomplexan parasites of public health concern. They are one of the main causes of intestinal diseases in humans and animals. Contaminated water is among the main sources of infection for humans and mammals. Raccoons are an introduced species in Germany. They are anthropogenic adapters with a natural affinity for water bodies. We collected samples from wild raccoons in the Federal States of Saxony and Thuringia, Central Germany. Through molecular genotyping, we found Cryptosporidium sp. skunk genotype in one raccoon from Saxony (1/24) and in one animal from Thuringia (1/27). Both raccoons were also infected with the zoonotic nematode Baylisascaris procyonis . This is the first report of co-infection with these two parasites in raccoons from Germany. Our study highlights the potential of these animals as carriers of zoonotic pathogens. Since raccoons can thrive in human settlements, this study provides data that can be used as a baseline for preventive programs.